Measuring early care and education quality in Peru: Validation of the CLASS toddler - Marta Dormal (International Journal of Educational Research Open)
Demand for Early Care and Education (ECE) services for children under three has increased in many Majority World countries, but research on how to measure ECE quality in these contexts is limited. This study investigated the measurement properties of the Classroom Assessment Scoring System Toddler version (CLASS-T) in its first application to Peru’s national ECE program for children under three, using data on 582 classrooms and educators and 2,198 children. Confirmatory factor analyses showed that the measure’s original framework had acceptable model fit with minor adjustments. Statistically significant (but small) positive associations between the CLASS-T domains were found with educators’ years of education and with children’s cognitive and fine motor skills, but not communication skills. Taken together, these findings showed that the CLASS-T may provide an appropriate option for measuring emotional and instructional support domains of toddler and infant ECE quality in a Peruvian sample. Implications for policy and practice are discussed.